AGE LIMIT FOR MARRIAGE IN LAW NUMBER 16 OF 2019 ON THE PRACTICE OF UNDERAGE MARRIAGE IN KARAWANG REGENCY - Destia Ayuning Thias; Muhamad Abas; Anwar Hidayat (HERMENEUTIKA : Jurnal Ilmu Hukum, 2023)
Underage marriages are marriages that do not meet the minimum age requirements stipulated in law number 16 of 2019 concerning amendments to law number 1 of 1974 concerning marriage. In law number 16 of 2019 article 7 it states that marriage is only permitted if a man and a woman have reached the age of 19. Based on the research results, it can be interpreted that the marriage rate in Karawang district has fluctuated since the enactment of law number 16 of 2019. This is evidenced by the percentage of underage marriage rates in Karawang district based on marriage dispensation data at the Karawang religious court. The data obtained is as follows, in 2019 there were 59 submissions, in 2020 there were 203 submissions, in 2021 there were 122 submissions and in 2022 there were 127 submissions. In addition, there are several factors that cause underage marriages in Karawang district, including arranged marriages, parents avoiding their children from committing adultery and even because they have already sent out invitations. There are some who are pregnant out of wedlock but the number is only a few in Karawang district. Legal research was conducted using an empiris juridical approach.